Pengaruh Pemberian Reward dan Punishment Terhadap Kinerja Karyawan Pada Perusahaan Pembongkaran Swasta Bekasi Timur - Andini Isma Aprilia Susanto; Dudi Akbar (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the effect of reward and punishment on employee performance at PT Nadia Rahma, it is important to understand these dynamics in improving the quality of human resources in the era of globalization. The methodology used is a quantitative approach with multiple linear regression, involving 48 employees selected using the saturated sample technique. The results show that reward has a positive and significant effect on performance, while punishment has a negative and significant effect. Simultaneously, these two variables affect performance by 18.4%. These findings are in line with previous research, but also highlight the negative impact of excessive punishment. This study adds novelty by identifying the percentage effect of reward and punishment, providing an in-depth insight into the interaction of the two variables in the context of demolition companies.